Apoptosis Induced via Gamma Delta T Cell Antigen Receptor “Blocking” Antibodies: A Cautionary Tale - Dutta, Indrani; Postovit, Lynne-Marie; Siegers, Gabrielle M. (Frontiers in Immunology, 2017)
Mechanistic studies contribute greatly to our understanding of γδ T cell (γδTc) biology, aiding development of these cells as immunotherapeutic agents. The antibody blocking assay is an accepted method to determine the receptors involved in γδTc killing of tumor targets. Effectors and/or targets are preincubated with microgram quantities of monoclonal antibodies (mAb), often described by commercial sources to be useful for blocking assays. We and others have used such assays extensively in the past, correlating decreases in cytotoxicity against specific targets with involvement of the blocked receptor(s). However, we wondered whether other mechanisms might be at play beyond cytotoxicity inhibition. Indeed, administration of certain “blocking” mAb to the γδ T cell antigen receptor (γδTCR) induced γδTc death. Upon further investigation, we discovered that γδTc underwent apoptosis triggered by incubation with mAb to the γδTCR. This effect was specific, as no apoptosis was observed when αβ T cells (αβTc) were incubated with these mAb. Apoptosis was further potentiated by the presence of interleukin (IL)-2, often included in cytotoxicity assays; however, exogenous interleukin-2 (IL-2) did not contribute significantly to γδTc cytotoxicity against breast cancer cell lines. Here, we have investigated the usefulness of four mAb for use in blocking assays by assessing blocking properties in conjunction with their propensity to induce apoptosis in cultured primary human γδTc. We found that the 5A6.E9 clone was usually a better alternative to the commonly used B1 (or B1.1) and 11F2 clones; however, some variability in susceptibility to apoptosis induction was observed among donor cultures. Thus, viability assessment of primary effector cells treated with mAb alone should be undertaken in parallel with cytotoxicity assays employing blocking antibodies, to account for cytotoxicity reduction caused by effector cell death. Previous findings should be reassessed in this light.